Secularism, Religion, and Politics: India and Europe - Losonczi, Peter (Ethics, Human Rights and Global Political Thought, 2014)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Foreword -- Introduction Religion, Democracy, and Secularism in Contexts: Dilemmas and Arguments -- Part I: Conceptualizing Contexts: The Secularism and Post-secularism Debates in India and Europe -- 1. Secularism: The Life and Times of a Difficult Concept -- 2. Contextualizing Secularism: The Relationship between State and Religion in India -- 3. Beyond Moderate Secularism -- 4. Secularism in Plural Post-colonial Democracies: Is Liberal Toleration Enough? -- 5. Religion, Pluralism, Politics: Case for an Inter-contextual Study on Europe and India -- Part II: Contextualizing Concepts: Between Secularism and Democracy in Europe, India, and Beyond -- 6. Religious Political Parties in Europe and India -- 7. Secular Pluralism in India: Lessons for Europe? -- 8. Secularism and the Spirit of Capitalism -- 9. Sri Lankan Post-coloniality, Secular Time, Future of Democracy -- 10. Shaping Secularism through the Judiciary in Nepal: Case Studies from the Kathmandu Supreme Court -- About the Editors -- Notes on Contributors -- Index